P-84 Crn west midlands initiative: making children's hospices research ready: the next steps. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Castro, Krys; Sheply, Hilary; Phipps, Marie
Abstract : Following on from our first poster that showcased the Clinical Research Network West Midlands (CRN WM) Children's Research Team's work from January 2016 and described processes established and training provided, as well as events, we are now presenting the progress from summer 2016. The main focus was the joining of the Children's Research Team with the Adult CRN West Midlands (WM) Supportive and Palliative Care Team and to build and combine a strategic plan. Part of the plan includes a bespoke training package for children's hospices as an introduction to research. Further training for hospices is being organised and will be rolled out in the near future. Attendance at the WM Paediatric Palliative Care Network (WMPPCN) enabled networking, and invitations to work with the chair of the WMPPCN raised the profile and identified research studies and increased awareness in children's hospices in the West Midlands. The WM Young Persons' Steering Group (YPSG) has assisted the chair of the WMPPCN with the design of the study including reviewing of the protocol, designing the patient and parent information sheets, study posters and other study supplements. In October 2016, the study opened in Birmingham Community Healthcare NHS Trust and Birmingham Children's Hospital. The next steps include hospice research studies. A first poster at the Hospice UK Conference: 'Making children's hospices research-ready' was presented. This enabled networking and invitations to collaborative groups and has resulted in the team identifying adult research policy and adapting them to children's settings. In conclusion, we will also be rolling out the research awareness training in children's hospices across the region. More work will be coming out from the research sub-group of the WMPPCN. The CRN West Midlands Supportive and Palliative Care Strategy will be revised to include the children's strategy for the region.